Use of geoprocessing for morphometric characterization of the São Martinho stream microbasin - TUPÃ-SP, Brazil - Campos, Marcelo [UNESP]; Campos, Sergio [UNESP] (Univ Federal Roraima, 2022)
This study analyzed the morphometric characteristics of the Sao Martinho stream microbasin, belonging to the municipality of Tupa (SP), applying geoprocessing using the Geographic Information System QGIS version 3.12.12. The microbasin located between latitudes 21 degrees 51' 49 and 21 degrees 58' 24 S and longitudes 50 degrees 20' 38 and 50 degrees 32' 44 W, has an area of 3612 ha. The Parnaso (SP) planialtimetric chart (IBGE, 1974), on a scale of 1:50000, was used as the cartographic base for delimiting the microbasin, drainage network extracting and contour lines. This microbasin was classified as being of 4th order, according to the hierarchy proposed by Arthur Strahler, being classified with a vocation for agriculture and pasture, due to its smooth undulating relief. The drainage density was classified from median to low and is not subject to flooding, but due to its circular shape to oval-shaped, it is prone to rapid flooding, favoring erosion. Due to these factors, there are risks of susceptibility to erosion and environmental degradation, being fundamental the maintenance of the vegetation cover and riparian zones for the conservation of environmental services in addition to conservationist measures.
Keywords: Geotechnologies; Sao Martinho stream microbasin; Morphometry